Proposal for a project management office characterization for a brazilian public university - Bonato, Samuel Vinícius (2020)
The need to improve tools, skills, and techniques shows the project management as an important instrument of development, organizational change and a way to reach the strategic objectives of organizations. In the Public Sector, more specifically the Education sector, this issues are constantly being discussed as a way to improve the control e the efficiency of resources use. This paper has as general objective to propose the characterization of a model of Project Management Office for the strategic projects in a Brazilian Federal University (UFB), focusing in identify in a literature review the most used PMO models and define which of them can be used in the University's PMO. Findings analyze the model that works best for the management of UFB's strategic projects and made possible several contributions that can bring benefits to the university. These contributions stand out: the ability to maximize the resources needed for the UFB; the capacity to generate knowledge in this area making possible great advances for the management of the university's strategic projects; the ability to generate tools that support decision making; the ability to provide support in processes increasing the success rate in projects.